2018
DOI: 10.3390/app8050744
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Mid-IR Laser Pulses Generation via Chirp Manipulated Optical Parametric Amplification

Abstract: Abstract:Over the past decades, optical parametric amplification (OPA) has become one of the most promising sources of ultrafast Mid-IR laser, owing to its outstanding properties including ultrabroad bandwidth, superior tunability, good beam quality, and scalable energy. In this paper, we review the recent progress in ultrashort laser pulse generation via chirp manipulated OPA, which improves the energy scalability and gain bandwidth by strategically chirping both pump and seed pulses. The gain mechanism is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…[50][51][52] IR spectroscopic insight to even faster phenomena, which occur at the femtosecond time scale, are enabled by the recent development of advanced laser pump-probe methodologies. [53][54][55][56][57] The range of mid-IR electromagnetic waves covers the B10-300 fs region, which defines the limit of time resolution that can be achieved by IR spectroscopy.…”
Section: Ftir Spectrometers -Basic Principlesmentioning
confidence: 99%
“…[50][51][52] IR spectroscopic insight to even faster phenomena, which occur at the femtosecond time scale, are enabled by the recent development of advanced laser pump-probe methodologies. [53][54][55][56][57] The range of mid-IR electromagnetic waves covers the B10-300 fs region, which defines the limit of time resolution that can be achieved by IR spectroscopy.…”
Section: Ftir Spectrometers -Basic Principlesmentioning
confidence: 99%
“…However, even an artificial material/structure with an unusually high nonlinearity is unlikely to provide high-gain OPA in the nanoscale for all the frequencies at a desired bandwidth without the maximization of the gain-bandwidth product through dispersion engineering. [2,4,[6][7][8][9] Hence, nanoscale OPA still remains a big challenge. In this article, it will be shown that the gain-bandwidth product of the OPA process can be drastically enhanced at the nanoscale through computational dispersion engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrashort laser pulses also play a large role in measuring the nonlinear response of materials to high intensity pulses. Ultrafast technologies have been used in a wide variety of applications, including pulse compression techniques for few-cycles pulses via self-phase modulation (SPM) [1][2][3], Kerr instability amplification [4,5], and generation of ultrashort pulses in the infrared (IR) and terahertz (THz) regimes [6][7][8]. Femtosecond pulse durations also allow for the investigation of processes that occur on femtosecond to attosecond (1 as = 10 −18 s) time scales, such as high harmonic generation [9,10] and femtosecond [11,12] and attosecond pump-probe experiments [13].…”
Section: Introductionmentioning
confidence: 99%